El voto como mecanismo obligatorio de participación y la cultura electoral en Ecuador - Pabón Vásquez, Cristiam Medardo (2021)
Democracy is based on the election of authorities who hold public office and represent citizens, through universal, direct and secret vote. This suffrage has several factors for which it is mandatory, in certain cases due to a weak culture of electoral participation, while in some countries with greater participation in elections, in addition to more information on the process and candidates, there is a vote. voluntary and is exercised with greater intervention. The objective of this article was to analyze the application of the compulsory voting law in Ecuador and its sanctioning measures as a measure to increase the electoral culture of the country, through a study with a qualitative, descriptive approach. The information was collected in addition to sources documentaries through the consultation of 6 experts in the field. The most important findings guide in the Ecuadorian case, that it is necessary that voting is mandatory to minimize electoral abstention and grant legitimacy to those elected and thus favor political stability and democracy, therefore sanctions for non-compliance and participation. of all the groups established in the Constitution and electoral laws strengthen the current culture of participation.